Acute interstitial nephritis and drug-induced systemic lupus erythematosus due to chlorthalidone and amiodarone: A case report. (February 2020) - Selamet, Umut; Hanna, Ramy M; Sisk, Anthony; Abdelnour, Lama; Ghobry, Lena; Kurtz, Ira
Drug-induced lupus erythematosus has features distinct from primary systemic lupus erythematosus. It can occur with a wide variety of agents that result in the generation of anti-histone or other types of antibodies. Systemic manifestations of drug-induced systemic lupus erythematosus may include renal dysfunction due to circulating immune complexes or due to other immune reactions to the culprit medication(s). Acute interstitial nephritis occurs due to DNA–drug or protein–drug complexes that trigger an allergic immune response. We report a patient who developed acute kidney injury, rash, and drug-induced systemic lupus diagnosed by serologies after starting chlorthalidone and amiodarone. A renal biopsy showed acute interstitial nephritis and not lupus-induced glomerulonephritis. It is important to note that systemic lupus erythematosus and acute interstitial nephritis can occur together, and this report highlights the role of the kidney biopsy in ascertaining the pathological diagnosis and outlining therapy in drug-induced lupus erythematosus.